Anonymous Traceability Protocol Based on Group Signature for Blockchain. (23rd March 2022) - An, Qi; Zhang, Yanhui; Guo, Chong; Liu, Ximing; Huang, Junjia; Zhang, Wenzhan; Zhang, Shijun; Zhan, Chao; Cai, Yuxiang
Abstract : In blockchain technology, data are stored on decentralized nodes and public to each node in the blockchain network. Hence, the focus of privacy protection in the blockchain guarantees the anonymity of transactions such that attackers cannot attain the users' personal information through data analysis. Among the existing privacy protection technologies, the scheme based on group signature has good anonymity, but the existing scheme exists a large number of operations that are difficult to apply to wireless terminals. In this paper, using the powerful offloading capability of edge computing, we propose a blockchain node traceable identity privacy technology scheme based on threshold group signature, and the scheme greatly reduces the computing burden of nodes while achieving node privacy protection.